Sohlh2 Inhibits the Malignant Progression of Renal Cell Carcinoma by Upregulating Klotho via DNMT3a - Liu, Yang; Cui, Weiwei; Zhang, Ruihong; Zhi, Sujuan; Liu, Lanlan; Liu, Xuyue; Feng, Xiaoning; Chen, Yanru; Zhang, Xiaoli; Hao, Jing (Frontiers in Oncology, 2022)
Background: Renal cell carcinoma is the most common malignant tumor of the kidney. The 5-year survival of renal cell carcinoma with distant metastasis is very low. Sohlh2 is a newly discovered tumor suppressor gene playing inhibitory roles in a variety of tumors, but its role in renal cell carcinoma has not been reported. Methods: To clarify the role of Sohlh2 in the occurrence and development of renal cell carcinoma, we constructed stably transfected human renal cell carcinoma cell lines with Sohlh2 overexpression and Sohlh2 knockdown, separately. First, we studied the effects of Sohlh2 on proliferation, migration, invasion and EMT of renal cell carcinoma cells in vitro and in vivo. Then, we detected whether Sohlh2 functions through DNMT3a / Klotho using western blot, qPCR and CCK-8 assay. Finally, we collected 40 resected renal cell carcinoma samples to study the relevance between solhlh2, DNMT3a and Klotho by immunohistochemistry. Results: Our results showed that Sohlh2 was down-regulated in renal cell carcinoma, and its expression level was negatively correlated with tumor staging. Both in vitro and in vivo experiments confirmed that Sohlh2 overexpression inhibited the proliferation, migration, invasion, metastasis and epithelial mesenchymal transformation (EMT) of renal cell carcinoma. Sohlh2 functions through demethylation of Klotho by down regulating the expression of DNA methyl transferase of DNMT3a. In renal cell carcinoma, Sohlh2 was positively correlated with Klotho and negatively correlated with DNMT3a. Conclusion: Sohlh2 functions as a tumor suppressor gene in renal cell carcinoma by demethylation of Klotho via DNMT3a. Sohlh2 correlated with Klotho positively and with DNMT3a negatively in renal cell carcinoma. Our study suggests that Sohlh2 and DNMT3a/Klotho can be used as potential targets for the clinical treatment of renal cell carcinoma.